2019
DOI: 10.32098/mltj.01.2018.01
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia induces osteogenic differentiation of bone marrow derived stem cells: an in vitro study

Abstract: Introduction: The physiopathology of calcific tendinopathy (CT) is largely unknown. It could be the result of an active cell-mediated process. Many endocrine and metabolic diseases may impair the homeostasis of the tendon. The present study investigated whether hyperglycemia may influence the differentiation of bone marrow MSCs (bMSCs). The hypothesis is that high glucose levels may induce bone differentiation of MSCs. Methods: Bone marrow (BM) was aspirated from the humeral head of three patients and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…differentiation is remarkable when MSCs are cultured with insulin too. 23 Oliva et al 24 recently focused on thyroid disorders and ruptures of rotator cuff tendons. A higher incidence of rotator cuff tears has been reported in patients with hypothyroidism, probably because of different proliferation capability of tenocytes in the presence of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…differentiation is remarkable when MSCs are cultured with insulin too. 23 Oliva et al 24 recently focused on thyroid disorders and ruptures of rotator cuff tendons. A higher incidence of rotator cuff tears has been reported in patients with hypothyroidism, probably because of different proliferation capability of tenocytes in the presence of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…115 In addition, in vitro insulin treatment of TSPCs increased the formation of mineralization modules and increased the expression of osteogenic genes such as Runx2, ALP, and osteonectin (OSN). 112,116 Thus, TSPCs derived from diabetic rat tendons demonstrate enhanced osteogenic and chondrogenic differentiation and suppressed tenogenic differentiation, which are likely to affect the tendon repair and facilitate the progression of diabetic tendinopathy. An in vitro study by Xu et al, reported that increased AGEs reduced cell viability, increased apoptosis and autophagy, induced senescence, and enhanced ossification in mouse Achilles TSPCs (Figure 1).…”
Section: Introductionmentioning
confidence: 99%